Enhance Mg-based heat storage materials kinetics by complex oxides. (December 2021) - Wu, Daifeng; Li, Rui; Sun, Tai; Tang, Renheng; Xiao, Fangming
Abstract: Mg/MgH2 as a thermochemical energy storage (TCES) material suffers from a slow hydrogenation-dehydrogenation kinetic and poor reversibility. Addition of metal oxide is an effective way to improve the kinetic properties of Mg/MgH2 . However, there is little study on the effects of complex oxides. Thus, the catalytic effects of complex metal oxides and its catalytic mechanism were investigated in this paper. Results show that the dehydrogenation peak temperature and apparent activation energy of MgH2 -Ta2 O5 are 320.8 °C and 128.54 kJ/mol. Combined with complex metal oxide, MgH2 -Ta2 O5 -Nd2 O3 could further reduce the dehydrogenation peak temperature (307.2 °C) and apparent activation energy (95.33 kJ/mol). MgO and NdH2.61 are found in the dehydrogenated MgH2 -Ta2 O5 -Nd2 O3, indicating that n-typed oxide Ta2 O5 and p-typed oxide Nd2 O3 are formed and improved the kinetics properties of MgH2 . Furthermore, Nd2 O3 /Ta2 O5 interface is formed and acted as "p-n junction". When heating, the "p-n junction" is exposed to thermal radiation and produce electrons and holes, and then the kinetics properties of MgH2 are further enhanced. Graphical Abstract: ga1 Highlight: MgH2 -Ta2 O5 shows relative low dehydrogenation peak temperature and fast kinetics. N-type metal oxides semiconductor Ta2 O5 was formed, which can produce electrons to enhance the desorption of MgH2 . Compared to MgH2 -Ta2 O5, MgH2 -Ta2 O5 -Nd2 O3 shows better dehydrogenation peak temperature and kinetic properties. Nd2 O3 /Ta2 O5 interface was formed and acted as "p-n junction", leading to the excellent kinetic properties.